Hemorrhagic shock influence on colonic anastomoses in rats: evaluation of rupture by liquid distension resistance test - Pereira,Yara Ematne Amaral (2008)
PURPOSE: To evaluate the effect of hemorrhagic shock in colonic anastomoses in rats, with a rupture by liquid distension resistance test. METHODS: Wistar lineage rats, averaging 90 days old and weighing from 310 to 380 grams were divided into two groups. In the first group (G1), 10 animals were submitted to colonic anastomoses in normovolemic terms and the second group (G2), of 10 animals, was submitted to colonic anastomoses in hypovolemic conditions. The shock was caused by half milliliter of blood withdrawn, every two minutes, until the value of average 50mmHg arterial pressure or a total volume corresponding 30% withdrawal of volemia was reached. Serum lactate dosages were carried out at the beginning and end of the procedure. The average serum lactate values at the end of the surgery were 1.91 mmol/l in G1 group and 3.69 mmol/l in G2 group (p<0.05). On the fifth postoperative day, the animals were euthanized. The anastomoses were evaluated with a rupture by liquid distension resistance test. RESULTS: In G1, the average value of colonic rupture was 160.7 mmHg whereas in G2 it was 152.1mmHg (p>0.05). CONCLUSION: Hemorrhagic shock, under the established conditions of this study, had no influence on colonic anastomoses in rats evaluated with the rupture by liquid distention resistance test.